2019
DOI: 10.1534/g3.119.400215
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Genome Sequence Assembly of Dwarf Coconut (Cocos nucifera L. ‘Catigan Green Dwarf’) Provides Insights into Genomic Variation Between Coconut Types and Related Palm Species

Abstract: We report the first whole genome sequence (WGS) assembly and annotation of a dwarf coconut variety, ‘Catigan Green Dwarf’ (CATD). The genome sequence was generated using the PacBio SMRT sequencing platform at 15X coverage of the expected genome size of 2.15 Gbp, which was corrected with assembled 50X Illumina paired-end MiSeq reads of the same genome. The draft genome was improved through Chicago sequencing to generate a scaffold assembly that results in a total genome size of 2.1 Gbp consisting of 7,998 scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 130 publications
(178 reference statements)
7
48
1
Order By: Relevance
“…The most abundant class of SSRs identified from GBS sequences in this study was dinucleotide repeats. Similar results regarding abundant classes of coconut SSRs have been reported previously 42 . The most frequently identified type of dinucleotide repeat in the present study was AG/CT, similar to that identified for gene-based SRRs in a previous report 8 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most abundant class of SSRs identified from GBS sequences in this study was dinucleotide repeats. Similar results regarding abundant classes of coconut SSRs have been reported previously 42 . The most frequently identified type of dinucleotide repeat in the present study was AG/CT, similar to that identified for gene-based SRRs in a previous report 8 .…”
Section: Discussionsupporting
confidence: 91%
“…The most frequently identified type of dinucleotide repeat in the present study was AG/CT, similar to that identified for gene-based SRRs in a previous report 8 . However, this dinucleotide category was different from that identified from a whole-genome assembly, which was AT/TA 42 . Our newly developed SSR markers were tested for their effectiveness by using them to assess the genetic diversity of a collection of 40 coconut accessions.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The draft genome of a tall accession (Hainan Tall) has been made available (Xiao et al, 2017), with a scaffold length of 2.20 Gb (N50 = 418 kb). Also, while the analysis of the Chowghat Green Dwarf (CGD) genome was underway, the genome of a Catigan Green Dwarf, consisting of 2.1 Gb (N50 = 570.49 kb) sequence, has been published (Lantican et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…RGAs have been widely studied and efficiently used for breeding of resistant crops against insect pests and diseases (Karthika et al, 2019). One way to predict RGAs in plants is through bioinformatics analyses of next-generation sequencing (NGS) genomic and transcriptomic data (Lantican et al, 2019; Neupane et al, 2018; Zhang et al, 2016; Karthika et al, 2019). With the advent of this technology, it is possible to unravel gene networks and develop molecular markers tagging economically important traits, reveal other molecular information such as intron-exon boundaries and presence of transposable elements, and discover novel biological processes (Goodwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%